Fifo Vs Average : Komparasi Perhitungan Harga Pokok Penjualan (Studi Kasus di Kantor Penjualan PT. Sinar Sosro) - Gusi Putu Lestara Permana; Ni Nyoman Vera Yulianingsih (Jurnal Widya Akuntansi dan Keuangan, 2024)
Denpasar Sales Office PT. Sinar Sosro is a customer sales location for companies that specialize in soft drinks, particularly tea-based drinks. For businesses to produce accurate Cost of Goods Sold calculations, the selection of product inventory valuation methods in calculating Cost of Goods Sold is critical. The purpose of this study is to compare the calculation of Cost of Goods Sold using the Average inventory valuation method to that of FIFO. In this study, the descriptive quantitative method was used. The results showed that the FIFO method produced a lower value than the Average method when calculating Cost of Goods Sold. According to existing theory, Cost of Goods Sold using the FIFO method is more realistic because inventory is recorded based on the products that enter first and in accordance with the product's price. Profit and loss will be affected by the difference in the calculation of cost of goods sold. As a result, if a company wants to maximize profits, it should use the FIFO inventory valuation method to calculate Cost of Goods Sold.